2016
DOI: 10.1109/tbme.2015.2464771
|View full text |Cite
|
Sign up to set email alerts
|

A Feedback Control Approach to Organic Drug Infusions Using Electrochemical Measurement

Abstract: This platform will contribute to high-performance TIVA application of intravenous propofol anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In the study, conducted by Myers et al in [32], a PID controller is triggered after the bolus injection is injected. A minor amount of fluctuation in drug concentration is observed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study, conducted by Myers et al in [32], a PID controller is triggered after the bolus injection is injected. A minor amount of fluctuation in drug concentration is observed.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the PI controller is tuned by using parameter 5 to control the closed-loop drug delivery. The parameter set employed in our simulation study is identified from the experimental and simulation parameters in [32]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consider the drug delivery system in biomedical engineering (e.g., the intravenous (IV) bag associated with the intravenous therapy), the mathematical model of which can be represented as follows [17, 24]: trueẋ1false(tfalse)=afalse(tfalse)x1false(tfalse)+bfalse(tfalse)x2false(tfalse), trueẋ2false(tfalse)=cfalse(tfalse)x2false(tfalse)+ufalse(tfalse), where the state x1false(tfalse)[]x1m,x1M and x2false(tfalse)[]x2m,x2M denote the drug concentration level and infusion rate of the human body, the control u ( t ) denotes the drug delivery rate to the human body. Note that it will cause severe discomfort of the human body if the state x exceeds the specified range.…”
Section: Application To Drug Delivery Systemmentioning
confidence: 99%
“…In this section, we will analyze the overall performance of the system under the proposed control (66). (24), and Q (63)-(64). Suppose that the system is subject to Assumptions 1-6, the control (66) can guarantee the uniform boundedness and uniform ultimate boundedness of the system Q.…”
Section: Performance Analysis Of the Proposed Controlmentioning
confidence: 99%